The Evolution of Community Benefit: Perspective on Progress Toward Purpose - Evashwick, Connie J.; Jackson, Penrose (Frontiers in Public Health, 2020)
To maintain exemption from federal taxes, non-profit hospitals in the USA are required to contribute to their communities an amount comparable to the taxes they otherwise would have paid. Since 2008, non-profit hospitals have had to file Form 990 Schedule H with the Internal Revenue Service (IRS) to document their “Community Benefit” (CB) activities. The purpose of this article is to present an overview of the evolution of hospitals' engagement with their communities and to examine how the policy enforced by the IRS has evolved. The IRS has not made explicit the assumptions underlying the CB policy. As a result, the evidence about the impact of CB policy and CB activities on the health of a community is sparse. Non-profit hospitals are spending millions of dollars in CB activities and reporting requirements annually, but if and how these expenses contribute to a community's health and well-being are unclear. Conceptual frameworks, such as logic models or Collective Impact models, could be used to explicate the assumed relationships. As the field has evolved and grown more complex, identifying and measuring the contributions of a single hospital or single program to the health status of a community have become more challenging. Collaboration—promoted by the IRS and CDC—has increased these challenges. Until assumptions about relationships are made explicit and tied to measurable goals, non-profit hospitals must continue to comply with IRS requirements but should use their own targets, metrics, and evaluations to ensure that the resources devoted to CB programs are being used cost-effectively.